(3cTa GdCSQGQ Yf Mce GdWjhQ hGdCRgGQs - (3YHO GdSdGe Hf CMeO Hf ZGfe GdfGHdSj GdebOSj, YR GdOjf,J (B678 (3g` s
(3ChdgG (B:s
(3hHYO, aEfj fXQJ HYjf GdJMbjb, aQCjJ HfhQ GdJUOjb hGdJhajb Cf cd eNdhb ebQ HhLhO GdNGdb, hcd UGeJ aj GdMbjbI fGWb s
(3BNQgG (B:s
(3jG bdH HTQGc CjGe GdQVG QLYJ hgPg GdOGQ HGdCMHGH bO LeYJ s
(3Vef eLehY , JQJjHgG (B: (3ef U (B192 - (3U(B250s
(3GfXQ aj GdLRA GdChd GdCQbGe (B686-688 (3COHs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B355 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B223 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B5 - (3U (B571s
Keywords: (3GdCOHs